2016
DOI: 10.1016/j.celrep.2016.04.083
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP3 Modulates the Interaction of Invasion-Associated Transcripts with RISC

Abstract: Summary Insulin-like growth factor 2 mRNA binding protein 3 (IGF2BP3) expression correlates with malignancy. But its role(s) in pathogenesis remain enigmatic. Here, we interrogated the IGF2BP3-RNA interaction network in pancreatic ductal adenocarcinoma (PDAC) cells. Using a combination of genome-wide approaches we identify 164 direct mRNA targets of IGF2BP3. These transcripts encode proteins enriched for functions such as cell migration, proliferation and adhesion. Loss of IGF2BP3 reduced PDAC cell invasivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 44 publications
8
85
2
Order By: Relevance
“…Sequestration into AGO2/ RISC-free mRNP granules may therefore be the principal mechanism of IMP3-mediated mRNA protection from let-7-dependent silencing. In contrast, in pancreatic ductal adenocarcinoma cells (PDACs), IMP3 was reported to compete with miRNAs for common binding sites in target mRNA 3 ′ UTRs but also promote association of mRNAs with AGO2/RISC, suggesting a function as a bimodal regulator of target mRNA stability (Ennajdaoui et al 2016). Taken together, these observations suggest that IMP1 and IMP3 may regulate mRNA stability by multiple mechanisms, including sequestration in RISC-free mRNP granules, protection from miRNA-dependent degradation by competing for common binding sites, and enhancement of degradation by recruitment of AGO2/RISC to target mRNAs.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequestration into AGO2/ RISC-free mRNP granules may therefore be the principal mechanism of IMP3-mediated mRNA protection from let-7-dependent silencing. In contrast, in pancreatic ductal adenocarcinoma cells (PDACs), IMP3 was reported to compete with miRNAs for common binding sites in target mRNA 3 ′ UTRs but also promote association of mRNAs with AGO2/RISC, suggesting a function as a bimodal regulator of target mRNA stability (Ennajdaoui et al 2016). Taken together, these observations suggest that IMP1 and IMP3 may regulate mRNA stability by multiple mechanisms, including sequestration in RISC-free mRNP granules, protection from miRNA-dependent degradation by competing for common binding sites, and enhancement of degradation by recruitment of AGO2/RISC to target mRNAs.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Cell context-specific events, such as the presence of other RBPs and miRNA expression repertoires that modulate IMP1 activity, may help determine whether IMP1 preferentially promotes polarity or migration. More recently, the loss of IMP3 was reported to reduce PDAC invasiveness (Ennajdaoui et al 2016). Numerous IMP3 targets related to invasiveness and implicated in focal adhesions, adherens junctions, actin cytoskeleton, and cell migration were identified by iCLIP in PDAC cells.…”
Section: Regulation Of Imp Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Chtf18 is the only conserved DNA methylation target gene that was identified in this Chapter, supporting a previous study that has demonstrated its conservation for DNA replication between yeast, flies and mammals (Berkowitz et al, 2008). Furthermore, Igf2bp3 is an important member of a critical upstream signalling pathway that drives cell proliferation (Ennajdaoui et al, 2016;Lederer et al, 2014, Chernoff, 1999. In particular, Igf2bp3 (Palanichamy et al, 2016;Schaeffer et al, 2010) and Ube2c (Bajaj et al, 2016;Chou et al, 2014;Shen et al, 2013;Shuliang et al, 2013) have been widely studied in various cancers, confirming their ability to promote cell proliferation.…”
Section: Discussionsupporting
confidence: 59%
“…Despite their different methodologies, RIP and CLIP can produce complementary data when used to study the same RBPs under similar conditions (van der Brug et al 2008;Sanford et al 2009;Kershner and Kimble 2010;Jungkamp et al 2011;Mukherjee et al 2011;Brooks et al 2015;Hansen et al 2015;Ennajdaoui et al 2016;Prasad et al 2016;Uren et al 2016). Therefore, our goal has been to combine aspects of both techniques to produce a single procedure that quantifies RBP-RNA interactions at the whole-transcript level and at the binding site level.…”
Section: Introductionmentioning
confidence: 99%